Talent management in small advanced economies - Michailova, Snejina; Ott, Dana L. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Talent is in short supply and global competition for it is fierce. This has made Talent Management necessary for organizational sustainability and for countries' well-being and wealth. Talent Management in Small Advanced Economies offers important and timely insights into talent management challenges and solutions, as well as strategies, practices, and activities of small advanced economies and their companies. These countries have been, and continue to be, very well represented among the most competitive countries in the Global Talent Competitiveness Index. Combining academic research with practitioner perspectives, the book uses a range of examples from countries, including Switzerland, Singapore, Norway and New Zealand, to explore the importance of talent and its management, and analyze the concerns faced by small advanced economies in their talent management processes. Key themes explored include: exclusive and inclusive talent management approaches, internal development and external acquisition of talent, and whether to tell employees that they are (not) considered talent. The use of practitioner insights alongside company case studies makes this book a unique and illuminating guide for scholars and professionals working within the areas of both Talent Management and Human Resource Management.
Introduction -- Chapter 1. Talent, talent management, and why they matter? -- Chapter 2. Talent management decisions -- Chapter 3. Talent management in small advanced economies -- Chapter 4. Talent management in New Zealand -- Conclusion.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Personnel management; Business & Economics -- Human Resources & Personnel Management; Personnel & human resources management